2011
DOI: 10.1007/s11738-011-0814-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of barley seedlings to water deficit and enhanced UV-B irradiation acting alone and in combination

Abstract: Responses of barley seedlings to water deficit (WD) induced by polyethylene glycol (PEG 6000) and ultraviolet (UV-B; 280-320 nm) radiation and their interaction (UV-B ? WD) were examined. A decrease in dry matter yield and water content of leaves and roots was observed following application of WD and UV-B ? WD, while no changes were found after treating barley plants with UV-B. Proline content was increased in leaves under WD conditions and UV-B ? WD. In contrast, UV-B treatment had no effect on the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 81 publications
2
28
0
2
Order By: Relevance
“…These general principles were confirmed in our study which demonstrated that the concentrations of cyanidin-3-O-galactosyl-rhamnoside and cyanidin-3-O-glucosyl-rhamnoside in the cotyledons of all tested buckwheat cultivars increased significantly under exposure to UV-B radiation. Similar results were previously noted in common buckwheat [7,25,28], Tartary buckwheat [31] and other plants [2,19,21].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These general principles were confirmed in our study which demonstrated that the concentrations of cyanidin-3-O-galactosyl-rhamnoside and cyanidin-3-O-glucosyl-rhamnoside in the cotyledons of all tested buckwheat cultivars increased significantly under exposure to UV-B radiation. Similar results were previously noted in common buckwheat [7,25,28], Tartary buckwheat [31] and other plants [2,19,21].…”
Section: Resultssupporting
confidence: 90%
“…Their presence in the walls of epidermal cells is generally associated with UV protection, whereas the presence of mesophyll cells in vacuoles and chloroplasts is linked with reactive oxygen species scavenging [1]. According to many reports, UV-B radiation increases flavonoid levels in young plants [2,19,21,25]. In this study, the concentrations of individual flavones indicate that the effect of UV-B is genetically determined ( Table 2).…”
Section: Resultsmentioning
confidence: 55%
“…However, the availability of water increases the phenolic compounds in tomato cultivars (Barbagallo et al, 2008) and barley (Bandurska et al, 2012). The mechanisms that regulate this influence are not completely clear, and there is variability in responses between species and cultivars.…”
Section: Total Antioxidant Activitymentioning
confidence: 99%
“…This variation was 29.4% (IPA-20) to 271.4% (F-21) (Figure 2). Generally the reduction in water addition increases the content of phenolic compounds and anthocyanins in plants, since these molecules act against water stress (Bandurska et al, 2012).…”
Section: Total Anthocyanin Contentmentioning
confidence: 99%
“…Degradation of cAMP and cGMP is catalyzed by more or less specific 3 0 ,5 0 -cyclic nucleotide phosphodiesterases (EC 3.1.4.17) (Pietrowska-Borek et al, 2014a). (4) Plant cells respond to stress by intensifying production of various phenylpropanoic compounds (Lawton et al, 1983;Dixon and Paiva, 1995;Liu and McClure, 1995), such as flavonoids (Winkel-Shirley, 2001;Olsen et al, 2008), lignins (Moura et al, 2010), anthocyanins (Steyn et al, 2002;Bandurska et al, 2012) and salicylic acid (Hayat Abbreviations: PAL, phenylalanine:ammonia lyase; 4CL, 4-coumarate:coenzyme A ligase; C4H, cinnamate-4-hydroxylase; CHS, chalcone synthase; CCR, cinnamoylcoenzyme A:NADP oxidoreductase; ICS, isochorismate synthase; NH 2 -pA, adenosine 5 0 -phosphoramidate; F-pA, adenosine 5 0 -monophosphofluoride; SA, salicylic acid; HIT proteins, superfamily of proteins that contain histidine-triad sequence motif. Bandurska and Cie slak, 2013).…”
Section: Introductionmentioning
confidence: 99%